SOSIALISASI PENINGKATAN KARAKTER MORAL DAN ETIKA ANAK DENGAN PSIKOEDUKASI BERBASIS SHORT MOVIE - Cahyani, Dian; Musyrif, Moh Tholhah; Manasikana, Arina; Nurfaradila, Elin; Putri. K, Isrotul Nur; Qonitatun. H, Rona; Dewi, Anisa Aulia; Khumairotin, Umi; Fatah, Dimas Kamal; Ilmi, Darul (Mafaza : Jurnal Pengabdian Masyarakat, 2025)
Childhood is a very vulnerable period where children begin to learn moral and ethical values ​​that will shape their personalities in the future. This community service program aims to develop psychoeducation through a short film entitled